PENGARUH PERPUTARAN KAS DAN PERPUTARAN MODAL KERJA TERHADAP RETURN ON INVESTMENT PADA PERUSAHAAN SUBSEKTOR MEDIA DAN ENTERTAINMENT YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2023 - Fitri Wahyuni Ramadhani; Dr. Yusriadi Hala, S.E., M.Si., M.Ak.; Nur Azizah Basmar, S.E., M.Acc (STKIP Subang, 2025)
This study aims to analyze and determine the effect of cash turnover and working capital turnover on Return On Investment in media and entertainment sub-sector companies listed on the Indonesia Stock Exchange in 2020-2023 using a quantitative descriptive approach. The type of data in this study is secondary data. The population in this study is all media and entertainment sub-sector companies listed on the Indonesia Stock Exchange in 2020-2023, totaling 19 companies. The sample in this study was 14 companies with a sampling method using purposive sampling technique and the data processed was 56 financial reports. The analysis techniques used in this study are classical assumption tests, multiple linear regression analysis and hypothesis testing using IBM SPSS Statistics Version 26. The results of the study show that the cash turnover variable has an effect on Return On Investment, while the working capital turnover variable has a negative effect on Return On Investment.